Variations in hemoglobin measurement and eligibility criteria across blood donation services are associated with differing low-hemoglobin deferral rates: a BEST Collaborative study - Zalpuri, Saurabh; Romeijn, Bas; Allara, Elias; Goldman, Mindy; Kamel, Hany; Gorlin, Jed; Vassallo, Ralph; Grégoire, Yves; Goto, Naoko; Flanagan, Peter; Speedy, Joanna; Buser, Andreas; et al. (Transfusion, 2020)
BACKGROUND: Determination of blood donor hemoglobin (Hb) levels is a pre-requisite to ensure donor safety and blood product quality. We aimed to identify Hb measurement practices across blood donation services and to what extent differences associate with low-Hb deferral rates. METHODS: An online survey was performed among Biomedical Excellence for Safer Transfusion (BEST) Collaborative members, extended with published data. Multivariable negative-binomial regression models were built to estimate adjusted associations of minimum donation intervals, Hb cut-offs (high, ≥13.5 g/dL in men or ≥ 12.5 g/dL in women, vs. lower values), iron monitoring (yes/no), providing or prescribing iron supplementation (yes/no), post-versus pre-donation Hb measurement and geographical location (Asian vs. rest), with low-Hb deferral rates. RESULTS: Data were included from 38 blood services. Low-Hb deferral rates varied from 0.11% to 8.81% among men and 0.84% to 31.85% among women. Services with longer minimum donation intervals had significantly lower deferral rates among both women (rate ratio, RR 0.53, 95%CI 0.33-0.84) and men (RR 0.53, 95%CI 0.31-0.90). In women, iron supplementation was associated with lower Hb deferral rates (RR 0.47, 95%CI 0.23-0.94). Finally, being located in Asia was associated with higher low-Hb deferral rates; RR 9.10 (95%CI 3.89-21.27) for women and 6.76 (95%CI 2.45-18.68) for men. CONCLUSION: Differences in Hb measurement and eligibility criteria, particularly longer donation intervals and iron supplementation in women, are associated with variations in low-Hb deferral rates. These insights could help improve both blood donation service efficiency and donor care.
Keywords: Hemoglobins; Blood Transfusion; železo; dárci krve; výběr dárců; hemoglobiny; průzkumy a dotazníky; krevní transfuze; Time Factors; lidé; ženské pohlaví; Iron; Humans; Donor Selection; Hematologic Tests; časové faktory; hematologické testy; Female; Surveys and Questionnaires; Blood Donors